Design, Efficient synthesis and molecular docking of some novel Pyrazole derivatives as anticancer agents - K.Banupriya; R.Girija (International Journal of Pharma and Bio Sciences, 2020)
Pyrazole is a multifaceted first position compound to representation formidable bioactive molecules for drug discovery and drug development, especially in cancer therapy. The goal of this research article is to present-day the most recent action in the area of synthetic path construct the functionalized pyrazole derivatives effective against proliferation cells. The research article covers the synthesis of 1H-pyrazole. Pyrazole derivatives were synthesized by using substituted chalcones. Chalcones are prepared by aromatic aldehydes and acetone in presence of ethanol in sodium hydroxide. Pyrazole derivatives possess various pharmacological and biomedical properties. Pyrazole derivatives act as an anticancer agent. In this research article pyrazole derivatives act as breast cancer agents. Insilico Molecular docking approach of Pyrazole derivatives analogue with the target protein from the 3D-Crystal structure (PDB ID: 4ZW1) was carried out using computational approach with Schrodinger Maestro 12.1. The aim of this study is to determine the activity of 9 Pyrazole derivatives, these compounds were obtained from the previous studies of breast cancer inhibitors and also to compare the activity of several pyrazole derivatives with the doxorubicin. Doxorubicin is used to stops the growth of cancer cells. Based on the docking results, it shows that five compounds have a greater potential to be used as an inhibitor of breast cancer cells than the other test compounds. Compound 16 has shown the best binding affinity energy of -9.0 kcal/mol, it is indicated that ligands perform a bonding with the receptor through the eleven active sites of doxorubicin. Compound 16 has shown the good binding affinity with target protein. Hence it has been concluded Compound 16 as a potent inhibitor for Breast cancer.